Treatment of malignant pleural effusion in non-small cell lung cancer with VEGF-directed therapy - Xiang, Zhangqiang; Deng, Xiangyu; He, Wenfeng; Yang, Qian; Ni, Laichao; Dehghan Shasaltaneh, Marzieh; Maghsoudloo, Mazaher; Yang, Gang; Wu, Jingbo; Imani, Saber; Wen, Qinglian (Annals of medicine (Helsinki), 2022)
Vascular endothelial growth factor (VEGF) is a critical regulator of malignant pleural effusion (MPE) in non-small-cell lung cancer (NSCLC). Bevacizumab (BEV) and apatinib (APA) are novel VEGF blockers that inhibit lung cancer cell proliferation and the development of pleural effusion. In this study, we established Lewis lung cancer (LLC) xenograft mouse models to compare the therapeutic effect of APA and BEV in combination with cisplatin (CDDP) against MPE. The anti-tumour and anti-angiogenic effects of this combination therapy were evaluated by 18 F-FDG PET/CT imaging, TUNEL assay and Immunohistochemistry. The triple drug combination significantly prolonged the overall survival of the tumour-bearing mice by reducing MPE and glucose metabolism and was more effective in lowering VEGF/soluble VEGFR-2 levels in the serum and pleural exudates compared to either of the monotherapies. Furthermore, CDDP + APA + BEV promoted in vivo apoptosis and decreased microvessel density. Mechanistically, LLC-induced MPE was inhibited by targeting the VEGF-MEK/ERK pathways. Further studies are needed to establish the synergistic therapeutic effect of these drugs in NSCLC patients with MPE. KEY MESSAGES Combined treatment of MPE with apatinib, bevacizumab and cisplatin can prolong the survival time of mice, reduce the content of MPE, decrease the SUV max of thoracic tumour tissue, down-regulate the content of VEGF and sVEGFR-2 in serum and pleural fluid, and promote the apoptosis of tumour cells. Angiogenesis and MPE formation can be inhibited by down-regulation of HIF-1α, VEGF, VEGFR-2, MEK1 and MMP-2 molecular signalling pathway proteins.